Leadership in rural congregations and communities: an exploration in the North-Eastern Free State - P. C. J. Nel; W. J. Schoeman (Acta Theologica)
Rural communities and congregations cannot simply be overlooked. Communities in the north-eastern Free State are typical rural towns with a strong emphasis on agricultural activities and less emphasis in terms of processing products and other activities. Over the past few decades, rural communities have experienced many changes in terms of depopulation, the decline of the rural economy, poverty, and unemployment. Congregations in rural communities and their leadership cannot escape these changes that affect their functioning and existence. The key research question is thus: What is the congregational leadership’s opinion and argument about leadership in both the congregation and the community? The research indicated that a shift is taking place as far as the minister’s role in the leadership of the congregation is concerned. The congregational leadership needs to develop a missional perspective that brings the wider community into the ministry of the congregation. Although there is an awareness in respect of the missional calling of the church and the congregation, the change is still limited and there is room for a greater and more deliberate involvement of the congregation and its leadership within the community.